Analisis Nilai Hasil pada Proyek Konstruksi Bangunan di Kota Jambi - Ambo Assa; Annisaa Dwiretnani; Dwitya Okky Azanna; Fadlan Fadlan (Universitas Batanghari Jambi, 2026)
This research evaluates the cost and schedule performance of the Skywalk Construction Project at Bhayangkara Hospital TK II, Jambi Regional Police, using the Earned Value Management (EVM) method. By integrating cost, schedule, and physical progress, EVM provides an objective basis for assessing project performance and forecasting completion. Analysis up to the 22nd week focused on the Cost Performance Index (CPI) and Schedule Performance Index (SPI). Results show that project costs were efficient during weeks 1–19 (CPI > 1), but experienced overruns in weeks 21–23 (CPI < 1). In terms of schedule, delays occurred in week 1 and weeks 17–22 (SPI < 1), while weeks 2–16 indicated accelerated progress (SPI > 1). The Estimate At Schedule (EAS) method predicted project completion in 150 days or 22 weeks, confirming a delay from the original schedule. Overall, the findings highlight the importance of continuous monitoring and control to improve cost efficiency and schedule adherence in construction project management.